Assessment of asymptomatic bacteriuria and sterile pyuria among antenatal attendants in hospitals in northern Ghana - Akosua Bonsu Karikari; Courage Kosi Setsoafia Saba; David Yembilla Yamik (BMC, 2020)
Abstract Background Asymptomatic bacteriuria (ASB) and sterile pyuria (SP) are complexities of UTI whose prevalence are not known in the northern sector of Ghana. Our aim was to determine the occurrence of sterile pyuria and asymptomatic bacteriuria among pregnant women accessing antenatal care at a secondary and tertiary care hospitals in Tamale, northern Ghana. Methods A cross sectional study was conducted by screening 530 pregnant women with no signs of acute urinary tract infection attending antenatal clinic for a period of 6 months. Midstream urine was collected for microscopy, quantitative urine culture and antibiotic susceptibility testing. Data analysis was carried out using the Statistical Package for Social Sciences version 20. Results Asymptomatic bacteriuria was respectively 20 and 35.5% at Tamale Central and Tamale Teaching Hospital out of the 390 and 90 women screened. Sterile pyuria was found among 66% of the 50 women presenting at Tamale Central Hospital. More than 64% of isolates recovered from ASB patients were S. aureus and coagulase negative Staph. (CoNS). Escherichia coli was the dominant species among members of the enterobacteriaceae isolated. Highest susceptibility was recorded against gentamicin and amikacin while most resistance was to Ampicillin, cotrimoxazole, chloramphenicol and nitrofurantoin. Resistance to imipenem and vancomycin were 28.8 and 52%, with strains showing multiple drug resistance of between 81 and 92%. Conclusion The prevalence of asymptomatic bacteriuria is appreciably higher (20-35.5%) than documented rates in the southern sector of the country. The presence of sterile pyuria which may be an indication of asymptomatic renal impairment and most often overlooked in antenatal management is 66%. Empirical treatment of UTIs at the Tamale Central and Teaching Hospital without confirmation of susceptibility may result in treatment failure. It is necessary to screen and treat pregnant women for ASB and SP due to the complications associated with these conditions.